Against the Demise of Discourse: Reclaiming Intellectual Culture in Indonesian Legal Education - Rafsi Azzam Hibatullah Albar (Universitas Negeri Semarang, 2025)
In many parts of the world, the field of law is seen as one of rigour and law schools are seen as melting pots of critical thoughts. Such used to be the case in Indonesia, but a quick look at the state of legal education in the country today would proffer an indication of otherwise. The increasing quota in law faculties nationwide is not matched with improved human capital output quality. In fact, law faculties have been derisively stereotyped as a dumpster for the laziest of students in prior education. This is frankly and very unfortunately not uncorroborated as reading, despite being a rudimentary and logically inseparable component of the typical law school experience, is missing as a habit. This is not to mention ensuing issues like a lack of critical exchange in classrooms and proficiency in the production of scholarly works. This paper exposes the problem in detail from the author’s experiences and observations which are still fresh in memory as a recent graduate from one of Indonesia’s (supposedly) best law faculties. Subsequently, the author posits several highlights of recommendations pertaining to creating a culture of intellectualism among students from his experimentative efforts as a teaching assistant and editor-in-chief of the oldest and foremost student-run law review in the country. A slow but steady process of habitualization is needed to accomplish the objective, employing various learning sources to increase learning appetite following three stages of one’s scholarly journey in law: reading, thinking, and writing. Taking an age-old confab to a long-overdue next phase, this paper focuses on providing practical insights for legal educators and fellow students, not just in Indonesia but also anywhere in the world who face the same predicament in their classrooms, to contribute in realizing meaningful change.